ANALISIS KANDUNGAN KAFEIN PADA KOPI SEDUHAN WARUNG KOPI DI KOTA BANDA ACEH - Elfa Riyanti; Ernita Silviana; Mela Santika (Lantanida Journal, 2020)
Coffee is the most popular beverage in the world after water and tea. In Acehnese society, the tradition of drinking coffee is passed down from generation to generation and has evolved into Aceh's unique cultural tradition, especially in Banda Aceh. However, behind its delicious taste, coffee drinkers need to be aware of the content of caffeine in coffee. According to SNI 01-752-2006, the limitation of caffeine consumption is 150 mg/day. The aim of the study is to measure the caffeine contents in gayo coffee and sareng coffee which brewed from coffee shops in Banda Aceh. This research was conducted at Akafarma Laboratory-Banda Aceh and at Research Laboratory Department of Chemistry FMIPA Unsyiah by using UV Vis spectrophotometry. The population in this study were Gayo coffee and Sareng coffee brewed in coffee shops in  Banda Aceh, whereas samples were taken by purposive sampling from coffee shops with the number of visitors above 200 people/day. The results showed that from ten samples of Gayo coffee that tested, two samples did not meet the SNI set requirements, namely samples 2 and 4, with the levels of each sample in one serving consecutively are 126.9 mg; 197.1 mg; 134.3 mg; 174.6 mg; 109.2 mg; 51 mg; 119.5 mg; 88.8 mg; 108.6 mg and 141.7 mg. On the contrary, in Sareng coffee, from the tests that conducted on 10 samples, the results showed that all of the samples meet SNI requirements, with the content of each sample in one serving consecutively is to 124.7 mg; 64.4 mg; 131.9 mg; 138.3 mg; 103.9 mg; 110.1 mg; 35.3 mg; 117.5 mg; 125.7 mg and 36.2 mg.